EFFORTS TO INCREASE THE MATHEMATICAL COMMUNICATION ABILITY OF CLASS VII-F MTsN 5 SUMEDANG STUDENTS’ IN LEARNING TRIANGLE THROUGH PEER TUTORING MODEL - Ade Kokom Mintarsih; Citra Megiana Pertiwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2020)
Abstract This research is motivated by the low Mathematical Communication Ability (MCA) of MTs students. To boost the improvement and achievement of student MCA, teachers need to create special formulations and design an effective strategies, methods, and techniques. This study aims to obtain an overview of the use of peer tutoring learning models on triangle material in improving MCA student in terms of students' minimum completeness criteria (KKM). The method used is classroom action research with the subject of the research being VII-F grade students in MTsN 5 Sumedang who are in Ujungjaya Sumedang with learning through 3 cycles consisting of the stages of planning, implementation, observation, and reflection in each cycle. The instrument used in this study was a written test in the form of MCA description questions which were carried out at the end of each cycle, observation sheets and interviews. The results of this study indicate that: 1) In each cycle the score of students under the KKM is decreases, 2) the learning can improve student MCA, 3) students are still difficult in connecting real objects, pictures, and diagrams into mathematical ideas. AbstrakPenelitian ini dilatarbelakangi oleh rendahnya Kemampuan Komunikasi Matematika (KKomM) siswa MTs. Guna mendongkrak peningkatan dan pencapaian KKomM siswa, guru perlu menciptakan formulasi khusus dan merancang suatu strategi, metode, dan teknik yang efektif. Penelitian ini bertujuan untuk memperoleh gambaran dari penggunaan model pembelajaran tutor sebaya pada materi bangun datar segitiga dalam meningkatkan KKomM siswa ditinjau dari Kriteria Ketuntasan Minimal (KKM) siswa. Metode yang digunakan adalah Penelitian tindakan kelas dengan subjek penelitian adalah siswa kelas VII-F di MTsN 5 Sumedang yang berada di Ujungjaya Sumedang dengan pembelajaran memalui 3 siklus yang terdiri dari tahap perencanaan, pelaksanaan, observasi dan refleksi pada setiap siklusnya. Instrumen yang digunakan dalam penelitian ini berupa tes tertulis berbentuk soal uraian KKomM yang dilaksanakan setiap akhir siklus, lembar observasi dan wawancara. Hasil dari penelitian ini menunjukkan bahwa: 1) Pada setiap siklusnya nilai siswa yang berada di bawah KKM semakin berkurang, 2) pembelajaran tersebut dapat meningkatkan KKomM siswa, 3) siswa masih sulit dalam menghubungkan benda nyata, gambar, dan diagram ke dalam ide matematika.